Somatosensory Loss Influences the Adoption of Self-Centered Versus Decentered Perspectives - Arnold, Gabriel; Sarlegna, Fabrice R.; Fernandez, Laura G.; Auvray, Malika (Frontiers in Psychology, 2019)
The body and the self are commonly experienced as forming a unity. Experiencing the external world as distinct from the self and the body strongly relies on adopting a single self-centred perspective which results in integrating multisensory sensations into one egocentric body-centred reference frame. Body posture and somatosensory representations have been reported to influence perception and specifically the reference frame relative to which multisensory sensations are coded. In the study reported here, we investigated the role of somatosensory and visual information in adopting self-centred and decentred spatial perspectives. Two deafferented patients that have neither tactile nor proprioceptive perception below the head and a group of age-matched control participants performed a graphesthesia task, consisting in the recognition of ambiguous letters (b, d, p, and q) drawn tactilely on head surfaces. To answer which letter was drawn, the participants can adopt either a self-centred perspective or a decentred one (i.e., centred on a body part or on an external location). The participants’ responses can be used, in turn, to infer the way the left-right and top-bottom letters’ axes are assigned with respect to the left-right and top-bottom axes of their body. In order to evaluate the influence of body posture, the ambiguous letters were drawn on the participants’ forehead, left, and right surfaces of the head, with the head aligned or rotated in yaw relative to the trunk. In order to evaluate the role of external information, the participants completed the task with their eyes open in one session and closed in another one. The results obtained in control participants revealed that their preferred perspective varied with body posture but not with vision. Different results were obtained with the deafferented patients who overall do not show any significant effect of their body posture on their preferred perspective. This result suggests that the orientation of their self is not influenced by their physical body. There was an effect of vision for only one of the two patients. The deafferented patients rely on strategies that are more prone to inter-individual differences, which highlights the crucial role somatosensory information plays in adopting self-centred spatial perspectives.